Development Evaluation Tool Two Tier Multiple Choice Using Wondershare Quiz Creator to Identify Mathematical Connection - Lestari, Sri Ayu; Zawawi, Irwani; Khikmiyah, Fatimatul; Fauziyah, Nur (Universitas Sembilanbelas November Kolaka, 2021)
The research objective is to develop anÂ evaluation tool two tier multiple choice using the wondershare quiz creator to identify students mathematical connection capabilities. The research model uses ADDIE. The test subjects in the study were class VII-D of Islamic Qon Middle School. The research instruments used were interview sheets, validation sheets, test instruments, and questionnaires. Data analysis techniques were carried out quantitatively and qualitatively. The results are: (1) the evaluation tool is feasible because it meets 2 valid and effective criteria. Valid criteria based on the assessment of media experts 94% (very feasible), and 80% material experts (feasible). Effective criteria are seen from the response of students and the quality of the items. The results of the students' responses were 82% (very interesting). While the quality of the items, the validity test contained 1 invalid question. Reliability test, there is 1 unreliable question. The difficulty level test has 7 moderate questions, 3 easy questions, and there are no difficult questions. The distinguishing power test contained 2 very good questions, 6 good questions, 2 enough questions, and not in the bad category. There were 11 distractors at the first level and 6 at the second level who were selected from all students. (2) The percentage of mathematical connections is very high 39.3%, high percentage 46.4%, moderate percentage 3.6%, low percentage 3.6%, and very low percentage 7.1%.